2021
DOI: 10.1055/s-0041-1736156
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine-Induced Hematological and Immunological Alterations in Egyptian Children with Idiopathic Generalized Seizures

Abstract: Carbamazepine (CBZ) is one of the oldest antiepileptic drugs (AEDs) that is still used for the treatment of tonic-clonic seizures in children. Long-term use of AEDs induces potential toxic effects that may remain undetermined for a long time. Earlier studies have revealed a wide spectrum of hematological toxicities associated with CBZ. This study was conducted to unveil the toxic effects of carbamazepine as an antiepileptic monotherapy on hematological and immunological parameters in a group of Egyptian pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A further 15% had sub-normal IgA levels. El-Shimi and colleagues found that IgA and IgM were lower than in 50 children with epilepsy treated with carbamazepine than in 15 controls [37]. In one longitudinal study of 19 patients with epilepsy, zonisamide was unlikely to affect immunoglobulin levels, but this study had low power [38].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 15% had sub-normal IgA levels. El-Shimi and colleagues found that IgA and IgM were lower than in 50 children with epilepsy treated with carbamazepine than in 15 controls [37]. In one longitudinal study of 19 patients with epilepsy, zonisamide was unlikely to affect immunoglobulin levels, but this study had low power [38].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Only one study has previously reported an exposure-response relationship between AED exposure and HGG. El-Shimi and colleagues found that IgG levels (but not IgA or IgM levels) were lower in children treated for longer with carbamazepine, but this analysis was hindered by a low sample size (only 50 children) [37].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%